Exploring the perceptions and experiences of community rehabilitation for Long COVID from the perspectives of Scottish general practitioners’ and people living with Long COVID: a qualitative study - Kay Cooper; Jenny Preston; Edward Duncan; Julie Cowie; Joanna Shim; Paul Swinton; Lyndsay Alexander; Jane Ormerod; Jacqui H Morris; Alison Love; Emma Stage; Tricia Tooman; et al. (BMJ Open, 2024)
Objectives To explore the experience of accessing Long COVID community rehabilitation from the perspectives of people with Long COVID and general practitioners (GPs).Design Qualitative descriptive study employing one-to-one semistructured virtual interviews analysed using the framework method.Setting Four National Health Service Scotland territorial health boards.Participants 11 people with Long COVID (1 male, 10 female; aged 40–65 (mean 53) and 13 GPs (5 male, 8 female).Results Four key themes were identified: (1) The lived experience of Long COVID, describing the negative impact of Long COVID on participants’ health and quality of life; (2) The challenges of an emergent and complex chronic condition, including uncertainties related to diagnosis and management; (3) Systemic challenges for Long COVID service delivery, including lack of clear pathways for access and referral, siloed services, limited resource and a perceived lack of holistic care, and (4) Perceptions and experiences of Long COVID and its management, including rehabilitation. In this theme, a lack of knowledge by GPs and people with Long COVID on the potential role of community rehabilitation for Long COVID was identified. Having prior knowledge of rehabilitation or being a healthcare professional appeared to facilitate access to community rehabilitation. Finally, people with Long COVID who had received rehabilitation had generally found it beneficial.Conclusions There are several patient, GP and service-level barriers to accessing community rehabilitation for Long COVID. There is a need for greater understanding by the public, GPs and other potential referrers of the role of community rehabilitation professionals in the management of Long COVID. There is also a need for community rehabilitation services to be well promoted and accessible to the people with Long COVID for whom they may be appropriate. The findings of this study can be used by those (re)designing community rehabilitation services for people with Long COVID.